Zakat: Konsep dan Peranannya dalam Pembangunan Sosial dan Ekonomi Masyarakat - Tasya, Ristiyanas; Putri Kayla Amanda; Salwa Nurul Azki (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Zakat is one of the pillars of Islam and plays a strategic role in creating spiritual and socio-economic balance among the people. As an instrument of Islamic economics, zakat serves to distribute wealth fairly, reduce social inequality, and empower the poor to achieve independence. This study aims to analyze the concept of zakat in Islam, its social and economic functions, and its implementation in the context of development in Indonesia. The research method used is qualitative descriptive with a literature study approach that examines primary sources such as the Quran and Hadith, as well as secondary literature from journals, BAZNAS reports, and previous research. Therefore, optimizing zakat requires a comprehensive strategy through digitizing the collection system, an empowerment-based productive approach, integrating national mustahik data, and synergy between the government, zakat institutions, and the private sector. With professional and empowerment-oriented management, zakat has the potential to become a crucial pillar in realizing sustainable socio-economic development and a just and prosperous society.